1988
DOI: 10.3346/jkms.1988.3.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Malignant tumors among Koreans-relative frequency study on 19,140 cases during 1978 to 1986

Abstract: A statistical analysis was made on 19,140 primary malignant tumors histopathologically diagnosed at Seoul National University Hospital during 9 year period from 1978 to 1986. The study was performed to understand the recent trend of the relative frequency of the primary malignant tumors among Koreans and to compare it with the previous studies using same hospital materials, twice presented in 1968 and 1978, respectively. Sex distribution of the cases was 10,025 (52.38%) males and 9,115 (47.62%) females. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Gastric cancer is prevalent in Korea; it is the most frequent malignancy and the leading cause of cancer death [1][2][3]. In recent years there has been an increasing tendency to perform total gastrectomy for the treatment of a high body or cardiac lesion, double lesions of gastric cancer, and recurrent cancer of remnant stomach.…”
mentioning
confidence: 99%
“…Gastric cancer is prevalent in Korea; it is the most frequent malignancy and the leading cause of cancer death [1][2][3]. In recent years there has been an increasing tendency to perform total gastrectomy for the treatment of a high body or cardiac lesion, double lesions of gastric cancer, and recurrent cancer of remnant stomach.…”
mentioning
confidence: 99%
“…It has been reported that the incidence of primary skin cancer among Asians including Korean is lower compared with the Caucasians ( 1 ). In Korea, the primary skin cancer comprises about 1.44% of all malignancies diagnosed annually ( 2 ) and its diagnostic rate has been estimated as 0.085 to 1.02% per all dermatology department visits with a recent continuous increase ( 3 - 9 ).…”
Section: Introductionmentioning
confidence: 99%